(untitled) (Jagannath University Journal of Arts, 2026)
Film is an important subject in the Bengali entertainment world in terms of art theory. In the late 19th century, cinema entered the entertainment world with the help of the Lumiere Brothers of Paris as a carrier of technological development. The tide of this development came to the Indian subcontinent with the help of filmmaker Hiralal Sen. Meanwhile, another legend of the subcontinent, Rabindranath Tagore, has roamed in all branches of literature in his life. In continuation of this, his great interest in films was also revealed. Along with the ease of acting in films, he also permitted to use his songs in films. Basically, according to the context of the story, the use of Rabindra Sangeet in the film scenes can be observed in a combination of emotion and art. Even in the case of various political changes in the country at different times, Rabindra Sangeet has been used as a message of movement through films. Over the years, not only commercial story-based films, but also films based on Rabindra’s stories have been used fluently. In keeping with the current era, the fluent use of Rabindra Sangeet in various story-based non-commercial films or art films is also noticeable. Although there are differences of opinion about the variety of instrumental accompaniment, this type of Rabindra Sangeet has gained considerable popularity among a certain generation. Such unhesitating use of Rabindra Sangeet in an attempt to make subcontinental films world-famous has taken the 21st century to another level. This article will show how much the unrivaled use and acceptance of Rabindra Sangeet in modern films has enriched the film world, including Rabindra Sangeet, through the efforts of filmmakers, artists, technicians, exhibitors, writers and other concerned parties. Jagannath University Journal of Arts, v-15, i-01, 2025:p54-64